Beginning of Fasting Based on the Javanese Aboge and Asapon Calendars - Prabowo, Agung; Amitarwati, Diah Paramita; Sukono, Sukono (International Journal of Ethno-Sciences and Education Research, 2022)
The Javanese calendar has been in use since July 8, 1633 AD, during the time of Sultan Agung. In the Javanese calendar, there is a cycle called kurup. Aboge is one of the kurup in the Javanese calendar, the third kurup after Awahgi and Amiswon. Currently, the Javanese calendar has reached the fourth circle, namely Asapon. Even though it is kurup, Aboge is special because Aboge is seen as a religious sect. Regarding determining the beginning of fasting and other religious holidays, Aboge has its own method based on the Javanese-Aboge Calendar, better known as the Aboge Calendar. This research was made to explain the inconsistency in determining the start of fasting calculated by the Aboge and Asapon calendars, compared to government regulations. The research method is a literature study and a case study surveying government regulation regarding the beginning of fasting and Eid al-Fitr. The study results show that both the Aboge Calendar and the Asapon Calendar are not appropriate when used as a guide for determining the implementation of religious holidays.